The Failure to Learn Lessons from Policy Failures in Developing Countries? The Case of Electricity Privatization in Ghana - Ohemeng, F.L.K.; Zaato, J.J. (International Journal of Public Administration, 2021)
Do policy makers learn from their failures? The rational and normal expectation would be that they do, but experience shows otherwise. Notwithstanding the valuable and multiply expected learning opportunities presented by such failures, especially in Africa, policy errors continue unabated in both the developed and developing worlds. Even the high-profile nature of the failures across the continent seems insufficient to convince African policy makers of their significance. Focusing on the In the recent electricity privatization fiasco in Ghana, this paper examines factors that impede or otherwise affect policy makers’ ability to learn from their mistakes. Using interviews with a number of officials involved in the process of electricity privatization, we identified five main factors that continue to affect policy learning from policy failures in Ghana
Research Article
Keywords: Policy failure; privatization; policy imposition